# 2(b-3)-3=3(b-6)

## Simple and best practice solution for 2(b-3)-3=3(b-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2(b-3)-3=3(b-6) equation:

Simplifying
2(b + -3) + -3 = 3(b + -6)
Reorder the terms:
2(-3 + b) + -3 = 3(b + -6)
(-3 * 2 + b * 2) + -3 = 3(b + -6)
(-6 + 2b) + -3 = 3(b + -6)
Reorder the terms:
-6 + -3 + 2b = 3(b + -6)
Combine like terms: -6 + -3 = -9
-9 + 2b = 3(b + -6)
Reorder the terms:
-9 + 2b = 3(-6 + b)
-9 + 2b = (-6 * 3 + b * 3)
-9 + 2b = (-18 + 3b)
Solving
-9 + 2b = -18 + 3b
Solving for variable 'b'.
Move all terms containing b to the left, all other terms to the right.
Add '-3b' to each side of the equation.
-9 + 2b + -3b = -18 + 3b + -3b
Combine like terms: 2b + -3b = -1b
-9 + -1b = -18 + 3b + -3b
Combine like terms: 3b + -3b = 0
-9 + -1b = -18 + 0
-9 + -1b = -18
Add '9' to each side of the equation.
-9 + 9 + -1b = -18 + 9
Combine like terms: -9 + 9 = 0
0 + -1b = -18 + 9
-1b = -18 + 9
Combine like terms: -18 + 9 = -9
-1b = -9
Divide each side by '-1'.
b = 9
Simplifying
b = 9